Hierarchical Ni–Co–O–C–P hollow tetragonal microtubes grown on Ni foam for efficient overall water splitting in alkaline media. Issue 45 (20th August 2019) - Hu, Wenjing; Jiang, Qingqing; Wang, Lin; Hu, Sha; Huang, Zhengxi; Zhou, Tengfei; Yang, Hai-Jian; Hu, Juncheng; Tang, Nanfang
Abstract : Herein, the Ni–Co–O–C–P hollow tetragonal microtubes grown on 3D Ni foam (Ni–Co–O–C–P/NF) was delicately designed and synthesized, which presented a high activity and durability for electrocatalytic overall-water-splitting in alkaline media. Abstract : Exploring low-cost and highly efficient non-noble bifunctional electrocatalysts with high performances for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is essential for large-scale sustainable energy systems. Herein, the Ni–Co–O–C–P hollow tetragonal microtubes grown on 3D Ni foam (Ni–Co–O–C–P/NF) was synthesized via a one-step solvothermal method and followed by a simple carbon coating and in situ phosphorization treatment. Benefiting from the unique open and hierarchical nano-architectures, the as prepared Ni–Co–O–C–P/NF presents a high activity and durability for both the HER and OER in alkaline media. The overall-water-splitting reaction requires a low cell voltage (1.54 V @ 10 mA cm −2 ) in 1 M KOH when Ni–Co–O–C–P/NF is used as both the anode and cathode. The highly flexible structure can provide a large amount of exposed active sites and shorten the mass transport distance. Furthermore, bimetallic phosphides also favor the electrocatalysis due to the higher electronic conductivity and the synergetic effect. This work demonstrated a promising bifunctional electrocatalyst for water electrolysis in alkaline media with potential in future applications.